Faktor yang Mempengaruhi Komunikasi Interpesonal Kepala Badan Sumber Daya Manusia Provinsi Bengkulu - Desy Puspita Indah (Journal Of Administration and Educational Management (ALIGNMENT), 2018)
This study aims to determine the factors that affect the effectiveness of interpersonal communication head of Human Resources Agency of Bengkulu Province. Research is designed as a qualitative research and uses descriptive data exposure. This data analysis technique is the step taken by researchers to interpret or provide meaning to the data that has been collected. The results of research In implementing interpersonal communication conducted by the head of the agency, it is seen that the effectiveness of communication is characterized by the openness in the implementation of activities, the attitude of supporting employees to improve performance, always trying to have a positive attitude towards all employees and equality in the execution of duties. Conclusion, because in our daily life in communicating interpesaonal is the basis to be able to communicate, where interpersonal communication can not be separated in the process of our daily life. Keywords: Effectiveness, Communication, Interpesonal